Optimisation of droplet size and pH for cosmeceutical cream containing virgin coconut oil (VCO) - Rulhisham, Nurul Syahirah; A Razak, Aliff Hisyam (Progress in Engineering Application and Technology, 2021)
The demand for herbal/natural-based cream and cosmetic is high due to non-toxic, almost no side effect, good skin result and many other advantages. This high demand of natural-based cream is resulted from reported case of bad effect by the consumers who utilise cream that contains harmful ingredients such as mercury, hydroquinone, lead, etc. for many purposes e.g. beauty, wound, irritation, skin allergy and weight loss. In Malaysia’s market, many of these harmful creams do not go a proper clinical test and this has led endangerment to the consumers. In this project, a stable water-based cream containing virgin coconut oil (VCO) as an oil phase is used as a base cream for cosmeceutical wound healing cream when incorporating an extract of Chromoleana odorata. Previous works had shown a stable cream i.e. no phases separation when incorporating 1% extract of Chromoleana odorata into VCO cream in a ratio of 90% water and 10% VCO. This project focused on the optimisation of oil droplet size in water-oil emulsion and pH when varying parameters such as ratio oil to water, emulsifier concentration and homogenizer speed via statistical methods i.e. Taguchi and Response Surface Method (RSM) by means of Design Expert software. A stable cream possesses microsized droplet and a good cream is suitable with human skin pH ranging from 5.5 to 6.5. Therefore, Taguchi criterion of droplet size was “the smaller is better” and while pH between 5.5 to 6.5 was chosen. The optimised droplet size and pH via Taguchi was compared to Response Surface Method (RSM) by means of Design-Expert software using central composite design to express the responses. The optimised droplet size and pH by Taguchi indicates that small droplet size and low level of pH occur when utilising 10%, 15% oil and 5:95 ratio oil to water, and when the percentage of emulsifier was at 1% and 5%. On the other hands, same percentage of oil and ratio oil to water as Taguchi method is obtained for small droplet size and low level of pH optimised by RSM while percentage of emulsifier used was 1% and 3%. The optimised droplet size and pH via Taguchi and RSM are rather different and hence validation on both droplet size and pH at abovementioned conditions need to be performed experimentally.